The Impact of a Demographic Trend on the Demand for Scheduled Bus Transport in the Slovak Republic - Gnap, Jozef; Konecny, Vladimir (Communications - Scientific letters of the University of Zilina, 2008)
Scheduled bus transport is an important and irretrievable transport system from society point of view. All age groups of population use this transport system to satisfy their own transport requirements. The performance of scheduled bus transport has markedly decreased recently. The performance level is affected not only by fare prices and incomes of population but also by the change in population structure. Population represents potential demand for scheduled bus transport services.